Transient human anti-mouse antibody generated with immune enhancement in a carbohydrate antigen 19-9 immunoassay after surgical resection of recurrent cancer. (July 2016) - Nakano, Keiichi; Yasuda, Keiko; Shibuya, Hitoshi; Moriyama, Takanori; Kahata, Kaoru; Shimizu, Chikara
We report a case of transient human anti-mouse antibody from a 64-year-old man in a carbohydrate antigen 19-9 immunoassay using an AIA 1800 analyser that generated immune enhancement after surgical resection of recurrent cancer. Methods: The carbohydrate antigen 19-9 concentration was measured using an AIA 1800 analyser and a UniCel Dxl 800. Size-exclusion high-performance liquid chromatography was carried out on a Superose 12 column to estimate the carbohydrate antigen 19-9 elution profile using an AIA 1800 analyser. To determine whether IgM in the patient contributed to the carbohydrate antigen 19-9 immunoassay, immunoprecipitation was performed. Furthermore, mouse immunoglobulins were added to the patient's serum to verify that the patient's IgM reacted with it. Results: The carbohydrate antigen 19-9 concentration was >400 and 9.5 kU/L using an AIA 1800 analyser and using a UniCel Dxl 800, respectively. In the single carbohydrate antigen 19-9 peak, the molecular weight corresponded to IgM by size-exclusion high-performance liquid chromatography on a Superose 12 column. In the immunoprecipitation reaction and addition of mouse immunoglobulins, there was interference for anti-human IgM and mouse immunoglobulins whose recoveries were 3.2 and 14.2%, respectively. These results indicated that IgM in the patient's serum interfered with the carbohydrate antigen 19-9 immunoassay using an AIA 1800 analyser. Conclusion: A novel transient human anti-mouse antibody generated with immune activation in a carbohydrate antigen 19-9 immunoassay using an AIA 1800 analyser was identified in a patient with rectal cancer after surgical resection. These findings demonstrate the importance of monitoring tumour markers in patients after treatment with mouse monoclonal antibody.